2023
DOI: 10.47191/ijsshr/v6-i7-53
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Influential Factors and Demographic Traits on the Digital Employee Experience in Oman's Telecommunications Industry

S. Porkodi,
Shahla Said Khamis Al Balushi,
Marwa Khalid Mohammed Al Balushi
et al.

Abstract: The purpose of this research is to investigate the impact of various influential elements and demographic characteristics on the digital employee experience, with a focus on the telecommunications sector in the Sultanate of Oman. The main objectives of the research are to assess the intensity of various elements such as digital tool usability, technology accessibility, training availability, leadership support, organisational culture, and working environment on the digital employee experience and to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A pilot study was performed to assess the DEX elements, including intensity of digital tool usability, technology accessibility, training availability, leadership support, organisational culture, and working environment, and to examine the relationship between DEX and employee demographic characteristics like gender, age, education level, work experience, digital literacy, and job tenure in Oman's telecommunications sector (Porkodi et al, 2023a). The results revealed that the usability of digital tools has a disproportionately large effect on the DEX, and all demographic characteristics, with the exception of gender, affect the digital experience of employees.…”
Section: Elements Of Dexmentioning
confidence: 99%
“…A pilot study was performed to assess the DEX elements, including intensity of digital tool usability, technology accessibility, training availability, leadership support, organisational culture, and working environment, and to examine the relationship between DEX and employee demographic characteristics like gender, age, education level, work experience, digital literacy, and job tenure in Oman's telecommunications sector (Porkodi et al, 2023a). The results revealed that the usability of digital tools has a disproportionately large effect on the DEX, and all demographic characteristics, with the exception of gender, affect the digital experience of employees.…”
Section: Elements Of Dexmentioning
confidence: 99%